A Community-Based Lifestyle-Integrated Physical Activity Intervention to Enhance Physical Activity, Positive Family Communication, and Perceived Health in Deprived Families: A Cluster Randomized Controlled Trial - Lai, Agnes Y. K.; Lam, Eliza Y. W.; Fabrizo, Cecilia; Lee, Dickson P. K.; Wan, Alice N. T.; Tsang, Jessica S. Y.; Ho, Lai-ming; Stewart, Sunita M.; Lam, Tai-hing (Frontiers in Public Health, 2020)
Background: Zero-time exercise (ZTEx) is an approach integrating simple strength- and stamina-enhancing physical activity into daily life. The study evaluated the effectiveness of a community-based lifestyle-integrated physical activity intervention using ZTEx to enhance participants' physical activity, family communication, perceived health and happiness, and family harmony. Methods: A parallel group, cluster randomized controlled trial was conducted in a sample of 673 participants from eight Integrated Family Service Centers in Hong Kong. The experimental group (n = 316) received a physical activity intervention. The control group (n = 357) received information on healthy eating. Both groups received three face-to-face intervention sessions (totalling 6 h and 30 min) and 16 text messages. The primary outcome was the change in days spent engaged in ZTEx. Secondary outcomes included changes in sitting time, days engaged in moderate or vigorous physical activities, family communication (encouraging and engaging family members in ZTEx), dietary habits, perceived health and happiness, and family harmony. Self-administered questionnaires were used at baseline and at 3, 6, and 12 months. Mixed effects models with intention-to-treat analysis was used. Results: Compared with the control group at 3 months, the experimental group showed significantly greater increases of 1.3 days spent doing ZTEx (Cohen's d: 0.60), 0.3 days spent doing moderate physical activity (Cohen's d: 0.08), 0.3 days encouraging family members to do ZTEx (Cohen's d: 0.16), and 0.7 days doing ZTEx with family members (Cohen's d: 0.39) during the 7 days prior. At 3 months, the experimental group also showed a significantly greater improvement in perceived health, by a score of 0.2 (Cohen's d: 0.14). The effect sizes ranged from small to medium, with similar intervention effects at the 6-month and 1-year assessments. Compared with the experimental group, the control group showed a significantly greater reduction of 0.4 days on which sweetened beverages were consumed (95% CI: 0.01, 0.9, p < 0.05, Cohen's d: 0.28). The qualitative results supported the quantitative findings. Conclusions: Our findings show that a community-based lifestyle-integrated physical activity (PA) intervention can enhance physical activity, family communication, and perceived health in deprived families in Hong Kong. Trial registration: The research protocol was retrospectively registered at the National Institutes of Health (identifier number: NCT02601534) on November 10, 2015.